TAXONOMIC POSITION of GUIRATINGIA MENDESI (MEGADESMIDAE) and THE EVOLUTION of PERMIAN ENDEMIC BIVALVE FAUNA of THE PARANA BASIN, BRAZIL - Simões, Marcello Guimarães [UNESP]; Anelli, Luiz Eduardo (Soc Brasileira Paleontologia, 2010)
The unusual bivalve Guiratingia mendesi is redescribed from the original material. Detailed analysis of hinge and muscle scars allows more refined designation of its taxonomic position and affinities to other Permian bivalves from the Parana Basin. Guiratingia mendesi is characterized by very small, anteriorly expanded shells, with a great number of muscle striae within the area delimited by the pallial line. A flattened area is noted alongside the commissure of shell. The presence of a triangular blunt tooth in the right valve allows its designation to Megadesmidae. The absence of accessory muscle scars "a" and "b" and pedal elevator indicate that the genus belongs to the Plesiocyprinellinae, a group of bivalves considered endemic to the Passa Dois Group. Guiratingia mendesi is found, however, in limestones of the Palermo Formation (Middle Artinskian), nearly 100 in below the base of the Irati Formation (Late Artinskian). Until now, it was believed that within the Permian succession of Parana Basin, pre-Irati bivalves were all gondwanic or cosmopolitan. Guiratingia mendesi was an endemic, active burrower that resembles Runnegariella fragilis from the Permian Teresina Formation. This indicates that during Palermo times restricted paleogeographic conditions have existed within the huge Parana epeiric sea, favoring endemicity, probably in marine bayments close to its margins. The presence of an anteriorly expanded shell in G mendesi is a condition also seen in other Mesozoic and Cenozoic anomalodesmatans, demonstrating the recurrence of shell forms in distinct lineages of this interesting group of bivalves.
Keywords: Bivalvia; Megadesmidae; Plesiocyprinellinae; Permian; Parana Basin; Palermo Formation